2021
DOI: 10.1088/1742-6596/1879/2/022012
|View full text |Cite
|
Sign up to set email alerts
|

Role of toll like receptor-9 (1237 T/C) gene polymorphism in patients with type 2 diabetes and diabetic foot ulcer

Abstract: This study aimed to evaluate whether (1237 T/C) polymorphism is related with diabetic foot ulcer in type-2 diabetes mellitus of Iraqi patients in Najaf city. Diabetic foot ulcer (DFU) is one of the most prevalent and serious diabetic complications. DFU accounts for about 15% of the diabetic population. It is commonly associated with the increased diabetic morbidities and mortalities. The type 2 diabetes is recognized by aberrations of glucose, lipid and protein metabolism. It is increasingly appreciated that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, a positive association was confirmed at the +1174 locus [29]. In the Iranian population, the rs352140 SNP was not associated with T2DM or DN [13]; however, this could be a result of small sample size. The rs352140 SNP was studied in Chinese children with T1DM, and a strong association was observed between the SNP and T1DM development [11].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, a positive association was confirmed at the +1174 locus [29]. In the Iranian population, the rs352140 SNP was not associated with T2DM or DN [13]; however, this could be a result of small sample size. The rs352140 SNP was studied in Chinese children with T1DM, and a strong association was observed between the SNP and T1DM development [11].…”
Section: Discussionmentioning
confidence: 80%
“…The relationship between TLR9 and diabetes, specifically T2DM, is well established [12,13,17]. The rs352140 SNP was studied in T1DM, and it was confirmed that the rs352140 SNP was connected with residual β-cell function [11].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation